Religion That Bears “The Greatest Swaie in Our Harts”: Richard Hooker’s Propositions and the Care of Souls - André Gazal (Religions)
Richard Hooker’s (1553–1600) magisterial defense of the Elizabethan Church, Of the Laws of Ecclesiastical Polity, argued cogently for the authority of natural law and tradition in determining the constitution and practice of the national church. However, Hooker’s magisterial work movingly extends his complex arguments regarding the structure and authority of the church into the concrete, practical matters of pastoral practice, which the author addresses especially in Books V and VI. This paper will argue that the “Propositions” of Book V, which introduce this section of Hooker’s work, serve together as a compendium of his pastoral theology that informs not only Book V but also Books VI and even VII. We will support this argument by way of close analysis of the “Propositions” followed by an examination of how Hooker applies them to representative sections of Books V, VI, and VII.